How do pacing strategies differ in elite versus nonelite female Two Oceans Ultra marathon runners - Mouton, Chanel (Department of Health and Rehabilitation Sciences, 2025)
Background: Ultramarathon running is becoming an increasingly popular sport with millions of runners participating annually in events hosted all around the world. Pacing is considered as one of the key determinants of ultramarathon running success. Optimal pacing allows a runner to selectively manage their running speed throughout the race, to prevent premature fatigue, as they aim to achieve their desired outcomes. Although previous pacing studies provide a strong scientific foundation for research on Olympic and Championship endurance running, less is known about pacing patterns during mass-participation events – especially when focusing on female running performance. Previous research found that faster, older, and female runners achieve superior outcomes in marathon running due to their ability to maintain even pacing during competition. In a race with a challenging geographical profile, such as the Two Oceans Ultramarathon, it is unrealistic to adopt an even pacing profile throughout the entire race. This prompted us to investigate the effect of elevation on the pacing patterns adopted by elite and progressively slower female runners who successfully completed the 56- kilometre road race. Aim: The aim of this study was to determine, analyse and compare the pacing profiles adopted by elite and non-elite female runners during the Two Oceans Ultramarathon from 2007 to 2018. Specific objectives: 1) To describe the pacing profiles displayed by the elite female runners. 2) To describe the pacing profiles displayed by the successively slower categories of female runners. 3) To compare how pacing profiles might differ between the elite and slower category runners. 4) To establish how the different categories of female runners adapted their pace in response to the flat and hilly sections of the race and compare how it varied between runners of different ability. Methods: A retrospective, descriptive study was conducted to investigate the pacing patterns of female runners who successfully completed the Two Oceans Ultramarathon from 2007 to 2018. Race results from 9 682 eligible runners were obtained from a publicly accessible archive (www.twooceansmarathon.org). Participants were categorised into seven distinct groups based on their overall finish time. Split times recorded at 28km, 42km, 50km and at the finish (56km) were used to calculate the segmental splits and overall mean race pace for each runner included in the study. The segmental race pace for progressively slower groups were analysed to establish how each group a) paced over the first half of the race; b) changed their pace in response to the elevation over the second half of the race; c) might differ in their pacing profile depending on their running ability. Results: All seven groups of runners slowed down during the race before speeding up toward the finish, thereby adopting an initial positive pacing pattern followed by negative pacing towards the end of the race. The analysis of segmental split and overall finish times showed that the fastest finishers started the race within 4% of their overall mean race pace (103.97%; 95% confidence interval = 102.74 lower level, 105.20 upper level) whereas the slowest finishers had the fastest start, running 8% faster than their mean race pace (107.98%; 95% CI = 107.83 - 108.14). This unrealistic early race pace forced the lesser runners to slow down, resulting in finishing speeds of 8% slower than their starting speed (92.42%; 95% CI = 92.22 - 92.62). In contrast, the strongest group finished within 4% of their starting speed (96.11; 95% CI = 94.52 - 97.71) by adopting a more sustainable early race pace. The fastest finishers were the youngest (33.6 ± 5.1; years ± SD) and the slowest finishers were the oldest (39.5 ± 8.7). The average finishing time was 06:04:52 ± 00:38:11 (hr:min:sec ± SD). Only 0.5% of runners finished in less than four hours (49 of 9 682 participants), whereas 56.4% of the runners (5 406 of 9 682 participants) required six hours or more to finish the race. Conclusion: The results of this study suggest that runners should adopt a patient, sustainable starting speed. Elite runners with a specific time-objective may benefit from a faster pace over the flat first half of the race, making up for time lost over the challenging second half of the race. Slower runners, whose primary goal is to finish the event, should aim for a more conservative approach, equal to their running ability. These recommendations allow for the even distribution of energy resources throughout the race, preventing premature fatigue and improving race outcomes. The findings in this study provide valuable insights into effective pacing strategies for ultrarunners, contributing to our understanding of optimising performance in endurance running events.